Transcatheter aortic valve implantation: latest evidence, gaps in knowledge, and future directions - Mafrica, Dario; Dziewierz, Artur; Dobrev, Dobromir; Pelliccia, Francesco (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2025)
Aortic stenosis (AS) remains the most prevalent valvular heart disease worldwide and is increasingly managed through transcatheter aortic valve implantation (TAVI). With the 2025 ESC/EACTS Guidelines lowering the age threshold for TAVI to 70 years, the focus has shifted from short-term survival to lifetime management, necessitating rigorous evaluation of device durability, coronary access, and biological valve degeneration. This review synthesizes the latest evidence-based strategies for TAVI, contrasting randomized trial data with long-term registry findings. We critically analyze the hemodynamic trade-offs between self-expandable valves and balloon-expandable valves, particularly in patients with small aortic annuli, where SEVs demonstrate superior indexed effective orifice areas and reduced rates of patient–prosthesis mismatch (SMALL-TAVI registry). We further examine the expansion of indications into complex anatomical subsets, including bicuspid aortic valves (BIVOLUTX, STABILITY) and pure aortic regurgitation, where dedicated anchoring mechanisms are required to mitigate the risk of valve migration. Procedural optimization is addressed through the “minimalist” TAVI pathway (BENCHMARK registry), which emphasizes conscious sedation and ultrasound-guided vascular access to reduce length of stay without compromising safety. Finally, we discuss emerging biomarkers (MMP-3, osteopontin) and the role of epicardial adipose tissue as novel predictors of structural valve deterioration, signaling a potential shift toward biological modulation of valvular disease.